Extraction and Quantitative Determination of Cannabidiol (CBD) Fraction from Cannabis Sativa Species - Soha Jamal (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cannabidiol (CBD), non-psychoactive cannabinoid, was extracted from Cannabis sativa leaves by using solvent extraction method followed by reflux condenser procedure. Physical and chemical properties of Cannabidiol (CBD) were determined. Various parameters and contents of extracted oil were analyzed. Two different samples were prepared by applying different conditions. Sample “A” was prepared by applying reflux condenser and sample “B” was prepared by soaking eaves in ethanol (solvent) for one week. Various parameters and contents of extracted oil were analyzed. TLC, UV, GC-MS, IR and HPLC techniques were applied for characterization of both samples and oil. Some tests were also performed for the detection of proteins, carbohydrates, Steroids, tannins, gums and mucilage. Acid value, saponification number and specific gravity were also calculation by applying titration method. The results of both samples were showing major differences. The CBD content was also different in both samples. Due to non-psychoactive nature of CBD, it is known as safe side of marijuana and has many therapeutic benefits